Llama unleashes the alpacalypse - Stutzman, Jonathan (Henry Holt Books and Company, 2020)
Llama clones his friend Alpaca in order to avoid cleaning up after himself, but while Llama is eating the day away the Alpacas he set loose are causing pandemonium.